Changes in expression of zn transporters and in superoxide dismutase activity in zn-supplemented high performance handball players - Molina López, J.; Florea, D. I.; Hogstrand, C.; Molina, J. M.; Chirosa, L. J.; Quintero, B.; Planells, E. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Zn had been described as an important mineral in sport population. Zn as antioxidant in exercise is a recognised property that may contribute to protect against free radicals and the effect on sport performance. Zn is a metal that requires transporters, called ZIP family ZnT to develop different functions into the cell. 24 transporters are involved mediating transport of Zn: ZnT family transporting within the cell, which modulate their intracellular concentration, and ZIP family, carrying out the Zn from the organelles, causing an increase in the Zn intracellular. They contribute to maintain Zn homeostasis. Gene expression may provide information or characterization and understanding of physiological and metabolic regulatory pathways of the responses to exercise. Methods: 14 professional handball players>18y, with intense training and nutrition education for 2 months, supplemented with 50%RDAs for Zn. Zn was measured by flame atomic absorption spectrometry (FAAS) in wet-mineralised erythrocyte samples. Zn intake (%RDAs) was recorded by 72 h-recall and processed with Nutriber® software. SOD activity was determined by an enzymatic-colorimetric method in blood cells. Blood was drawn in PAXgene™ Blood RNA Tubes. Relative expression was calculated by measuring two genes for gene ÄCp calibrator, using three housekeeping genes as standard (GAPDH, UBC and YWHAZ). Results 33% of subjects presented low Zn intake at the begining of the study. Zn intake was significantly increased (p<0.05) following supplementation being no influenced by nutritional education. Zn plasma levels showed significant differences after supplementation (p<0.05). There were no differences in Zn blood cells levels and SOD activity. Analysis of Zn transporters showed a significant increase in genes ZIP3(p<0.01), ZIP5(p<0.01), ZIP13(p<0.01) and ZIP14(p<0.001) expression, after supplementation. At baseline, there were correlations between dietary Zn and ZIP13(r=0.62,p<0.05) and ZIP14 transporters (r=0.69,p<0.05). Similarly, the values in plasma were correlated with ZIP11(r=0.82,p<0.01). A correlation was found between the levels of Zn in blood cells with ZnT7(r=0.61,p<0.05) at supplemented final point. Discussion: ZIP3, ZIP5, ZIP13 and ZIP14 transporters increased the expression after intervention with Zn, possibly due of the tendency to overexpression in poor condition, and could indicate that we have not yet achieved the optimum levels of demand for this mineral. Zn intake and values in blood cells correlated with ZIP11, ZIP13, ZIP14 transporters at baseline, suggesting that poor intake or low values of Zn in blood cells are associated with high-expression values, while at higher Zn intake and Zn in blood cells, is lower expression. This confirms the possible role of these transporters as biomarkers of Zn status in humans. Elite athletes should be monitored by a clinical-nutritional follow up to avoid deficiencies that alter antioxidant status in critical situations, so supplementation may be necessary to optimize athletic performance.